2018
DOI: 10.1126/sciadv.aao1054
|View full text |Cite
|
Sign up to set email alerts
|

Late formation of silicon carbide in type II supernovae

Abstract: Isotopic study of presolar grains shows supernova SiC dust condenses out of ejecta more than 2 years after the explosion.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
19
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 47 publications
3
19
0
Order By: Relevance
“…The detection of a 49 Ti excess in presolar SiC grains of SN origin, commonly referred to as X-grains, was interpreted by as evidence for the late formation of silicate carbide in type II SNe (Liu et al 2018). Detailed calculations show that 49 Ti must have been incorporated in the grains not sooner than 2 years after the explosion (Liu et al 2018), in agreement with theoretical calculations showing that SiC grains are late to form in the ejecta (Sarangi & Cherchneff 2015). Figure 2 shows that at that epoch more than 50% of the dust has already formed in the ejecta.…”
Section: The Growth Of Dust Mass In Sn Ejectamentioning
confidence: 99%
“…The detection of a 49 Ti excess in presolar SiC grains of SN origin, commonly referred to as X-grains, was interpreted by as evidence for the late formation of silicate carbide in type II SNe (Liu et al 2018). Detailed calculations show that 49 Ti must have been incorporated in the grains not sooner than 2 years after the explosion (Liu et al 2018), in agreement with theoretical calculations showing that SiC grains are late to form in the ejecta (Sarangi & Cherchneff 2015). Figure 2 shows that at that epoch more than 50% of the dust has already formed in the ejecta.…”
Section: The Growth Of Dust Mass In Sn Ejectamentioning
confidence: 99%
“…For instance, supernova SiC grains are systematically 15 N rich and 54 Fe poor with respect to model predictions. Recent simulations suggest that many isotopic features of supernova SiC and graphite grains can be reproduced by H-ingestion in the Herich shells, that is, by the presence of residual H during explosive He-burning in supernova models (Pignatari et al 2013;Liu et al 2016Liu et al , 2017Liu et al , 2018. An alternative to selective mixing suggests the formation of supernova SiC and graphite grains in the O-rich layers of a massive star during a type II supernova explosion, where radiation may play a key role in dissociating the very stable CO molecules, hence freeing C atoms (Clayton et al 1999(Clayton et al , 2001Clayton 2013).…”
Section: Supernova Grainsmentioning
confidence: 99%
“…However, several observational studies have presented evidence that dust formation must continue for years (Gall et al 2014, Wesson et al 2015, Bevan & Barlow 2016. Additional evidence for slow dust formation comes from studies of presolar dust grains in meteorites: Liu et al (2018) found that 49 Ti and 28 Si isotope ratios were consistent with dust forming after a significant fraction of 49 V (half-life 330 days) had decayed into 49 Ti, while Ott et al (2019) found that barium isotope ratios were consistent with silicon carbide dust grains having formed when a substantial fraction of 137 Cs (half-life 30 yr) had decayed into 137 Ba. Although the extraction of isotope ratios from presolar grains and the nucleosynthetic model adopted are both sources of significant uncertainty, these results also indicate that the bulk of the dust formation occurs years to decades after the supernova outburst.…”
Section: Introductionmentioning
confidence: 99%